2002
DOI: 10.1007/3-540-47967-8_46
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Shape Modeling for Automatic Face Localization

Abstract: Abstract. Many approaches have been proposed to locate faces in an image. There are, however, two problems in previous facial shape models using feature points. First, the dimension of the solution space is too big since a large number of key points are needed to model a face. Second, the local features associated with the key points are assumed to be independent. Therefore, previous approaches require good initialization (which is often done manually), and may generate inaccurate localization. To automaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 16 publications
(18 reference statements)
0
29
0
Order By: Relevance
“…A newer development in the sampling literature are data-driven proposal distributions which make use of the input data to form probably useful proposals (heuristics). DDMCMC methods have been used to segment images [21], do inference about a complex 3D scene using only monocular input [22], to infer the pose of a human body model [19] or to localize faces [15].…”
Section: Markov Chain Monte Carlomentioning
confidence: 99%
“…A newer development in the sampling literature are data-driven proposal distributions which make use of the input data to form probably useful proposals (heuristics). DDMCMC methods have been used to segment images [21], do inference about a complex 3D scene using only monocular input [22], to infer the pose of a human body model [19] or to localize faces [15].…”
Section: Markov Chain Monte Carlomentioning
confidence: 99%
“…The results showed that the exploration of the multi-modal posterior was suboptimal using the standard MCMC techniques. The use of data-driven and mode-hopping MCMC schemes for better exploration of the posterior should be investigated [8,9]. Better models of the shape-free appearance also need to be incorporated in this framework.…”
Section: Discussionmentioning
confidence: 99%
“…Others model each object as one point in the high-dimensional feature space and increase the dimension to match the augmented complexity [21]. Both methods are inefficient and inadequate for human faces, where dramatic variabilities are exhibited due to the absence of feature semantics and lack of structural flexibility.…”
Section: Related Workmentioning
confidence: 99%